Serum neurofilament light chain in myasthenia gravis subgroups: An exploratory cohort and case–Control study - Stascheit, Frauke; Aigner, Annette; Mergenthaler, Philipp; Hotter, Benjamin; Hoffmann, Sarah; Lehnerer, Sophie; Meisel, Christian; Meisel, Andreas (Frontiers in Neurology, 2023)
Background This study aimed to evaluate the association of neurofilament light chain (Nfl) with neuromuscular destruction and disease severity in the serum of patients with myasthenia gravis (MG). Materials and methods Sera from 134 patients with MG with varying degrees of disease severity and autoantibody (Abs) status were analyzed and compared to controls in a cross-sectional design. Prospectively, we additionally measured serum NfL (sNfl) levels in patients with MG longitudinally for up to 3 years. Based on linear regression, differences between patients and controls were assessed. With correlation coefficients and mixed linear regression, the association among sNfl levels, socio-demographics, disease activity (Quantitative Myasthenia Gravis (QMG) score and Myasthenia Gravis Activities of Daily Living (MG-ADL) scale), Abs-status (acetylcholine receptor antibody (AChR-Abs), muscle-specific receptor tyrosine kinase antibody (MuSK-Abs), lipoprotein-related protein 4 (LRP4), and seronegative), Abs titer, treatment regime (pyridostigmine, steroids, and immunosuppressive therapies), and thymectomy were investigated. Results sNfl levels were higher in patients with MG compared to controls (median: 11.2 vs. 7.88), where sNfl levels were highest in anti-AChR-Abs positive patients (median 12.6), followed by anti-MuSK-Abs positive, anti-LRP4-Abs positive, and seronegative patients. Adjusting for age and sex, sNfl levels of patients with MG were on average 35% higher compared to controls (35.1, 95% CI: 8.4;68.3) and highest for patients with seronegative MG (44.35; 95% CI 16.47; 78.90). We found no relevant relationship between individual changes in sNfl and changes in QMG and MG-ADL scores. Conclusion sNfl levels are higher in patients with MG than in controls but were not consistently associated with clinical severity. Thus, sNfl is not a suitable biomarker to monitor individual disease progression in patients with MG.